Ide dan Gagasan Filsafat Humanis Master Cheng Yen - Hotmatua Paralihan (Sekolah Tinggi Agama Islam Sumatera Medan, 2017)
Master explains in world there is no one I do not love, no one I do Not believe, no one I do not forgive. Love is infinite and eternal. Once born in this world, every one has to face the problems of life and death ; we must face the problem of separation in the life and death. The world of the death is clearly displayed all around us, because inpermanence and suffring wil always come in this world. Rather than worrying about the matter after death. It is better to keep life at this moment, for what seed is planted, the fruit of the seed also to be harvested. This is also the same as the concept of the truth which Confucius once said :”if the meaning of life is not yet known, how to know the meaning of the death.”